AFTERSHOCK GAME: Bermain dan Belajar Mitigasi Gempa Bumi dengan Cara yang Menyenangkan - Titi Pambudi Karuniawaty; Adnanto Wiweko; Ajeng Hardanti; Intan Karmila; Nurul Imaniaty As-Syarifiah (Jurnal Gema Ngabdi, 2020)
Indonesia's position in the ring of fire and the great earthquake experience on Lombok Island a while ago led to the education and mitigation of earthquakes is very important.  These two things should be introduced early on and carried out continuously. The mitigation of earthquakes in school-age children will be more effective through a fun game as learning activity as well as educational tools. Aftershock Game is a non-digital card game specially designed to teach players to take attitudes quickly and precisely in the event of an earthquake. Playing activities while learning by using Aftershock Game has been conducted at MI Tazhib Kekait, one of the earthquakes affected locations. 90 elementary school children on 3rd-5th grade played this game as disaster mitigation education. This game was conducted in 15 small groups of 4-6 people. Activities are accompanied by a facilitator for 15-20 minutes per group, then at the end of each game students are required to give feedback on the Aftershock game. The performance of the game's aspect assessment shows that Aftershock Game is easy to play, fun and has high replay ability with a mean score of 8.89 out of a maximum score of 10. The game's design aspect also shows good value (mean score 8.32). Repairs are required on illustration and packaging boxes to be more durable when used. Educational materials on the earthquake and the mitigations are well delivered, with comprehensive content (mean score 8.82). Aftershock Game is an earthquake education game that is easy to play, interesting and comprehensive. This game is suitable for school aged children and can be developed as a community educational tools regarding the mitigation of earthquakes